Examining the antecedent of green entrepreneurship intention in business university students case of Indonesia - Virza Utama Alamsyah; Camelia Regista; Gede Herry Arum Wijaya (Institute of Computer Science (IOCS), 2023)
With the demands of the Paris Declaration and the national agenda of pursuing carbon neutrality by 2050, Green Entrepreneurship is the right way to accelerate this agenda into reality This study was made to examine what are the drivers of green entrepreneurship intentions in Indonesia, especially among business students. This research is based on the phenomenon that there are many students majoring in business or economics who have an entrepreneurial interest and also have a tendency to run an environmentally friendly business. This study applied a quantitative approach with a questionnaire as a measurement instrument, a total of 126 respondents were obtained from snowball sampling who were active students majoring in business, accounting, business, and economics. The finding in this study is that educational support and conceptual support influence and encourage students' self-efficacy which leads to the birth of green entrepreneurial intentions. The contribution of this research is that education and sustainability awareness are the driving factors for these young entrepreneurs to go green. Furthermore, the research found that the state's efforts to support these green entrepreneurs are at a low level, causing many students to be pessimistic and lack confidence in the progress of green industries.